2021
DOI: 10.24036/tip.v14i1.386
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Information System for Data Collection of Covid-19 Symptoms for Indonesian Citizens

Abstract: Information systems are the result of rapidly emerging technological developments because human needs as information users of technology are very strong and rapid. Begin with the very rapid growth of computer technology, computers such as smartphones, tablets, notebooks and others are limited in scale. This small computer device must be connected to the Internet so that it can be used properly. And the information system plays its role as a provider of information that computer users want to access when the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Staffing at the Faculty of Education State University of Surabaya. Thamrin et al [25] also shows that web application development developed based on the YII framework to collect data on Covid-19 symptoms in Indonesian society is very effective, with a percentage of 90.5 %. Zarlis et al [26] also showed relevant results, namely the YII framework-based application as a medium used to input final project scores or student theses at universities proved effective and efficient.…”
Section: B Discussionmentioning
confidence: 99%
“…Staffing at the Faculty of Education State University of Surabaya. Thamrin et al [25] also shows that web application development developed based on the YII framework to collect data on Covid-19 symptoms in Indonesian society is very effective, with a percentage of 90.5 %. Zarlis et al [26] also showed relevant results, namely the YII framework-based application as a medium used to input final project scores or student theses at universities proved effective and efficient.…”
Section: B Discussionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Thamrin juga menunjukkan bahwa pengembangan aplikasi web yang dikembangkan dengan basis yii framework untuk mengumpulkan data gejala Covid-19 di masyarakat Indonesia sangat efektif dengan persentase 90, 5% (Thamrin, et al, 2021). Hasil penelitian yang dilakukan oleh Zarlis juga menunjukkan hasil yang relevan, yaitu aplikasi berbasis yii framework sebagai media yang digunakan untuk menginput nilai tugas akhir atau skripsi mahasiswa di perguruan tinggi terbukti efektif dan efisien (Zarlis, et al, 2019).…”
Section: Pembahasanunclassified